Controllable Modular Growth of Hierarchical MOF‐on‐MOF Architectures. Issue 49 (8th November 2017) - Gu, Yifan; Wu, Yi‐nan; Li, Liangchun; Chen, Wei; Li, Fengting; Kitagawa, Susumu
Abstract: Fabrication of hybrid MOF‐on‐MOF heteroarchitectures can create novel and multifunctional platforms to achieve desired properties. However, only MOFs with similar crystallographic parameters can be hybridized by the classical epitaxial growth method (EGM), which largely suppressed its applications. A general strategy, called internal extended growth method (IEGM), is demonstrated for the feasible assembly of MOFs with distinct crystallographic parameters in an MOF matrix. Various MOFs with diverse functions could be introduced in a modular MOF matrix to form 3D core–satellite pluralistic hybrid system. The number of different MOF crystals interspersed could be varied on demand. More importantly, the different MOF crystals distributed in individual domains could be used to further incorporate functional units or enhance target functions. Abstract : A general strategy, the internal extended growth method (IEGM), was applied to design modular hierarchically structured MOF composites, thereby overcoming the limitation of lattice matching. The number of MOF crystals interspersed and the size of the MOF matrix can be well‐controlled. IEGM can optimize the design of novel multicompositional MOFs systems with great flexibility. TTIP=Ti(O i Pr4 ), BDC=benzenedicarboxylic acid.